Unconventional Charge‐Two Weyl Phonons in High‐Symmetry Lines - Xiang‐Feng Yang; Qing‐Bo Liu; Zhe‐Qi Wang; Hua‐Hua Fu (Advanced Physics Research, 2023)
Abstract Weyl phonons have long been regarded as an important kind of topological bosonic quasiparticle states. Previous investigations in this field mainly focus on Weyl phonons located at high‐symmetry points (HSPs) in Brillouin zone (BZ), while those located at high‐symmetry lines (HSLs, not including HSPs) are still rarely studied. Considering that their symmetry‐protected conditions are much different, we name them conventional and unconventional Weyl phonons, respectively. In this work, taking charge‐two Weyl phonons (CTWPs) as examples, the complete classifications of all unconventional CTWPs is summarized by performing symmetry analysis in all 230 space groups (SGs). Moreover, due to their different phononic dispersions, the unconventional CTWPs can be classified as Type‐I, Type‐II, and Type‐III ones. Particularly, the k · p model of unconventional CTWPs shows a k‐type feature along the invariant lines while a k2‐type feature along other directions. Additionally, we uncover that a real chiral crystal material, that is, CsBe2F5 in SG 213, can exhibit well‐defined Type‐I and Type‐II unconventional CTWPs characterized by multiple double‐helicoid surface states. Our theoretical work not only puts forward an effective way for seeking for unconventional CTWPs, but also uncover the unique advantages of this kind of CTWPs toward realistic device applications.